Sexual violence and associated factors among high school female students in Debre Markos Town, East Gojjam Zone, Northwest Ethiopia, 2021 - getinet, mamaru (Ethiopian Journal of Reproductive Health, 2022)
Background: Sexual violence against females takes many forms, including rape, sexual harassment such as asking for unwanted sex as a joke, kissing, touching sensitive parts such as the breasts, and threats. It affects all young women, regardless of their age or location. It has several sexual and reproductive health issues, including STDs, HIV/AIDS, unwanted pregnancies, abortion, and other issues. As a result, the goal of this study was to find out how common sexual violence against women is among Debre Markos high school students, as well as the factors that influence it. Methodology: Institutional based cross-sectional study was conducted among high school female students at Debre Markos Town, East Gojjam Zone. A self-administered questionnaire was used to collect data from 372 individuals selected by systematic random sampling technique from four governmental owned schools found in the town. The data were checked, coded, and entered into Epidata V 4.6 then exported into SPSS version 21 for analysis, then crude and adjusted OR were analyzed using logistic regression, and the level of significance of association was determined at P-value < 0.05. Results: Findings of this study showed that the lifetime prevalence of sexual violence and lifetime and current year attempt/completed rape was 110 (29.6%), 18 (4.8%), and 11 (3%) respectively. The mean age of respondents was 15.75 (SD±1.375) years. From the respondents who encountered sexual violence, the majority of the respondents were victimized by their boyfriend/husband 9(50%) and much older than their age minimum age 20 and maximum age 26 with a mean age of 23.75 years. Factors associated with sexual violence were family control (AOR = 22.14, 95% CI 10.58-46.30), the habit of drinking alcohol (AOR = 0.386, 95% CI 0.189-0.788), academic performance, age of respondents (AOR = 0.246, 95% CI 0.064-0.943) and permanent residence (AOR = 2.922,95% CI 1.175-7.265). Conclusion: Even though comparing the current study result to other study results conducted in the same study area was the difficult prevalence of sexual violence in this study area was high. The family control, the habit of alcohol intake, academic performance, permanent residence, and age of the respondents were identified as the main associated factors for sexual violence of female students in the study area. This needs further intervention like awareness creation at school and community settings, empowering girls in different activities at school and higher institutional level. Keywords: Sexual Violence, Prevalence, Factors, Female Students, Ethiopia